Population characteristics of the sea urchin Diadema antillarum in La Parguera, Puerto Rico, 17 years after the mass mortality event - Weil, Ernest (2005)
Recent reports indicate that populations of the black sea urchin Diadema antillarum are slowly coming back in several localities in the Caribbean after 15 years of absence. In La Parguera, Puerto Rico, urchins were totally absent from reef localities until 1996, when isolated, medium size individuals were observed in shallow reef habitats. To assess the status (distribution, densities and size structure) of populations of D. antillarum 17 years after the die-off, twelve 20 m² (10 x 2 m) band transects in each of four depth interval (0-3, 3-7, 7-11 and >11m) in each of four fringing coral reefs, and six-eight band-transects in each of two depth intervals (0-3 and > 3m) in three lagoonal mounds were surveyed in 2001. All urchins present in the band transects in two depth intervals (0-3 and 3-8 m) were collected and measured (test diameter) in situ to determine the average size and size (age) structure of populations. Overall, average densities were low and not significantly different (F=1.29, p= 0.125) across reef sites (0.83-1.39 ind/m²) and the seagrass mounds (1.09 ± 0.6-1.30 ± 0.6 ind/m²). Urchins were only found in the shallow areas (<3 m) on the seagrass mounds where they formed tight aggregations during daytime. Densities decreased significantly with increasing depth (r2 = -0.60) in reef sites and were significantly higher (F= 5.97, p<0.001) in shallow reef platforms (0.89 ± 0.69 – 1.98 ± 0.65 ind/m²) (0-3m), and the upper fore-reef (0.56 ± 0.14 – 2.33 ± 1.1 ind/m²) habitats (3-7m), compared to deeper (>7m) habitats (0.01 ± 0.02 – 0.88 ± 1.06 ind/m²). Enrique reef had a significantly higher (K-W, H= 165.19, p<0.001) population average size (Median= 7.7) compared to all other sites. Populations in the sea grass mounds were dominated by midsize to large individuals. Within reefs, the average size did not vary significantly across depth intervals with medium to large size urchins dominating. Higher number of aggregations and higher number of urchins per aggregation were correlated with low complexity (rugosity) habitats (Pearson’s r= -0.772, p<0.001 and r= -0.778, p<0.001 respectively), which supports the idea that this behavior provides protection. Although average densities were well below pre-mass-mortality densities in Puerto Rico, results of this study indicate that Diadema seem to be making a slow come back in La Parguera. Rev. Biol. Trop. 53(Suppl. 3): 219-231. Epub 2006 Jan 30.